Opacity of University Curriculum in Chile - González Ramírez, Isabel Ximena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The text analyzes the strategies of university curricular policies in three socio-his-torical periods: one of a socialist government, another of a long period of dicta-torship and a period of democratic transition, which lead to the opacity of the curriculum in Chile, through a qualitative, descriptive and critical methodology. allusive to the critical analysis of official speeches of each era. What allowed to identify and describe the neoliberal ideological elements that underpin the current educational policy in Chile, going from the unification of state education to the exponential growth of private universities and finally, to the consolidation of the supremacy of educational companies with their own curricula and representatives of certain groups of power, developing a sectoral policy referred to management.